Thermogenic Adipose Redox Mechanisms: Potential Targets for Metabolic Disease Therapies - Ashley K. Putman; G. Andres Contreras; Emilio P. Mottillo (MDPI AG, 2023)
Metabolic diseases, such as diabetes and non-alcoholic fatty liver disease (NAFLD), have several negative health outcomes on affected humans. Dysregulated energy metabolism is a key component underlying the pathophysiology of these conditions. Adipose tissue is a fundamental regulator of energy homeostasis that utilizes several redox reactions to carry out the metabolism. Brown and beige adipose tissues, in particular, perform highly oxidative reactions during non-shivering thermogenesis to dissipate energy as heat. The appropriate regulation of energy metabolism then requires coordinated antioxidant mechanisms to counterbalance the oxidation reactions. Indeed, non-shivering thermogenesis activation can cause striking changes in concentrations of both oxidants and antioxidants in order to adapt to various oxidative environments. Current therapeutic options for metabolic diseases either translate poorly from rodent models to humans (in part due to the challenges of creating a physiologically relevant rodent model) or tend to have numerous side effects, necessitating novel therapies. As increased brown adipose tissue activity results in enhanced energy expenditure and is associated with beneficial effects on metabolic health, such as decreased obesity, it has gathered great interest as a modulator of metabolic disease. One potential reason for the beneficial health effects may be that although non-shivering thermogenesis is enormously oxidative, it is also associated with decreased oxidant formation after its activation. However, targeting its redox mechanisms specifically to alter metabolic disease remains an underexplored area. Therefore, this review will discuss the role of adipose tissue in energy homeostasis, non-shivering thermogenesis in adults, and redox mechanisms that may serve as novel therapeutic targets of metabolic disease.